New Evidence of Loan Loss Provisioning Behavior under Basel Accord III: The Case of Chinese Commercial Banks - WEI, JUN JIA (2017)
Abstract: Examining all available commercial banks’ loan loss provisioning behavior in the period from 2011 to 2016, this paper mainly explores whether the new regulatory capital requirements and forward-looking provisioning system (dynamic provisioning) in Basel accord III, introduced by China’s banking regulatory commission in 2011, have impact on the commercial banks’ motives of earnings smoothing, capital management, moral hazard and counter/pro-cyclicality provisioning behavior. Using dynamic panel data and the Generalized Method of Moments (GMM) estimators to model loan loss provisioning behavior and using the technique of stochastic frontier analysis and the method of Maximum Likelihood Estimation (MLE) to estimate one of the independent variables of cost efficiency, this research documents that: from micro-economic level, commercial banks have raised concern of establishing forward-looking provisioning system to mitigate the pro-cyclicality effect on business cycle and when banks are challenged with the losses derived from high risk profiles in off-balance sheet, establishing forward-looking provisioning system helps banks to smooth the fluctuations of their earnings. Furthermore, the evidence also corroborates the finding of Bryce et al (2015) that GMM estimators in LLP model are biased when excluding cost efficiency scorers at the industry-specific analysis. There is no proof to support the motive of capital management via LLP and analyzed banks in the investigated period do not show the tendency of moral hazard.